Affecting Factors over Repurchase Shop Intention at E-Commerce Industry - Daniel Hero Fersil Punuindoong; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2020)
The purpose of this research to analyze the direct effect of use perceived ease, trust, and enjoyment consumer airy rooms over application. This research method is analysis descriptive with causality model to obtain the correlation between variables. In this research we use Structural Equation Models (SEM) with Lisrell apps as a testing tool. The population of this research in airy rooms users around 103 respondents. The result shows that perceived ease of use cannot increase a customer repurchase intention through the application of airy rooms, however the perceived ease of use can increase customer trust and enjoyment by using the airy rooms application. Trusted feels can’t increase a customer intention to use the airy room’s application. Furthermore, enjoyment in use airy rooms’ applications can lead customer repurchase intention.